119k views
0 votes
Please Help!!!! I really need this FAST

Please Help!!!! I really need this FAST-example-1
User ILevi
by
5.5k points

2 Answers

6 votes

Answer:

A

Explanation:

Let's solve your equation step-by-step.

7x−4+8x=6x+8

Step 1: Simplify both sides of the equation.

7x−4+8x=6x+8

7x+−4+8x=6x+8

(7x+8x)+(−4)=6x+8(Combine Like Terms)

15x+−4=6x+8

15x−4=6x+8

Step 2: Subtract 6x from both sides.

15x−4−6x=6x+8−6x

9x−4=8

Step 3: Add 4 to both sides.

9x−4+4=8+4

9x=12

Step 4: Divide both sides by 9.

9x9=129

x=43

User Vygintas B
by
5.6k points
5 votes

Answer:

B) x = 4/3

Explanation:

7x - 4 +8x = 6x + 8

7x + 8x - 6x = 8 + 4

7x + 2x = 12

9x = 12

x = 12 / 9

x = 4/3 ( got this answer by giving by 3rd table)

User Angel Hadzhiev
by
5.6k points